Effects of aerobic exercise training on the arterial stiffness and intramyocellular or extramyocellular lipid in overweight and obese men. (18th May 2020) - Park, Jiyeon; Choi, Youngju; Myoenzono, Kanae; Yoshikawa, Toru; Tagawa, Kaname; Isobe, Tomonori; Saotome, Kousaku; Sankai, Yoshiyuki; Shimojo, Nobutake; Maeda, Seiji
ABSTRACT: Intramyocellular lipid (IMCL) and extramyocellular lipid (EMCL) of ectopic fat in muscles are associated with arterial stiffness in normal-weight individuals. Furthermore, aerobic exercise training-induced changes in IMCL or EMCL content are related to a decrease in arterial stiffness in elderly people. Though arterial stiffness is strongly related with obesity, but the effects of aerobic exercise training on IMCL or EMCL content, with a particular focus on arterial stiffness, in obese individuals remains unclear. Here, we investigated the effects of aerobic exercise training on IMCL or EMCL content and arterial stiffness in obese individuals. First, in a cross-sectional study, we examined the relationship between arterial stiffness and IMCL or EMCL content in 24 overweight and obese men. Secondly, we investigated the effects of aerobic exercise intervention on arterial stiffness and IMCL or EMCL content in 21 overweight and obese men. In the cross-sectional study, EMCL content was positively correlated with baPWV and β-stiffness index, whereas IMCL content was negatively correlated with baPWV. In the intervention study, there were no significant changes in baPWV, β-stiffness index, and IMCL and EMCL contents after aerobic exercise training. However, exercise-induced change in baPWV and β-stiffness index were positively correlated with changes in EMCL content. Moreover, the group of improvements in baPWV was only correlated significantly with reduced EMCL content. These results suggest that IMCL and EMCL contents may affect arterial stiffness in overweight and obese men.